Activity restriction vs. self‐direction: hospitalised older adults' response to fear of falling. (7th January 2013) - Boltz, Marie; Resnick, Barbara; Capezuti, Elizabeth; Shuluk, Joseph
<x xml:space="preserve">Abstract</x> Background Functional decline is a common complication in hospitalised older adults, associated with low mobility and physical activity. Fear of falling may contribute to limited mobility and physical activity, and loss of physical function. An understanding of this relationship, as well as contributing factors, may inform the development of safe, function‐promoting interventions. Aim To describe fear of falling in hospitalised older adults and its relationship with patient characteristics and physical function and explore patient views of associated factors. Design combined quantitative and qualitative approach using chart extraction, observation and interviews of older adults. Methods (i) correlations and analysis of variance methods; (ii) content and thematic analysis; and (iii) evaluation of convergence, complementarity and dissonance of quantitative and qualitative data. Results Depressed older persons were more likely to describe fear of falling (r = 0.47, P = 0.002). Fear of falling was associated with the loss of physical function from admission to discharge (F = 7.6, P = 0.009). The participant response to fear of falling was activity restriction vs. self‐direction. Participants described the following factors, organised by social–ecological framework, to be considered when developing alternatives to activity restriction: intrapersonal, interpersonal, environmental and policy. Conclusion Fear of falling plays a significant role in restricting physical activity and function. A multifactorial approach may provide a viable alternative to activity restriction, by facilitating self‐direction and functional recovery. Implications for practice Interventions to prevent falls and activities to promote functional mobility are ideally developed in tandem, with attention paid to the physical and social environment. Preventing hospital‐acquired disability may require a shift in organisational values around safety, from a soley protective approach to one that reflects an enabling philosophy emphasising independence and self‐direction. Such a paradigm shift would demonstrate a valuing not only of the absence of falls but also the preservation and restoration of function.